Equally Subordinated? The Threat of a Self-Subordinating Way of Life on One's Moral Powers - (:unkn) unknown (My University, 2024)
Even in a politically just liberal state where citizens are ensured equality and certain basic liberties, citizens may still act in self-undermining ways that cause them to fail to exercise their liberties. I argue in this paper that because most conceptions of political liberalism only secure full freedom and equality within the basic structure, the background culture is left ripe with opportunities for identity-based self-subordination in associations and relationships. Freedom of association allows for citizens to adopt ways of life that may result in their own subordination (e.g., a woman adopting a sexist religion). I argue that when citizens adopt self-subordinating ways of life, they effectively place their “two moral powers” at risk of erosion over time. Citizens may (a) reduce their engagement with the principles of political justice and (b) their capacity to rationally pursue and revise their conceptions of the good may erode over time. I argue that if a citizen’s freedom and equality is at risk of being severely undermined by adopting a self-subordinating way of life, the state is justified in implementing certain limited paternalistic restrictions on, or incentives against, adopting those ways of life.